1949
DOI: 10.1139/cjr49f-041
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ten Electrical Meters for Determining Moisture Content of Wheat

Abstract: Ten electrical moisture meters were tested with 159 samples of Canadian hard red spring wheat, of Grades 1, 2, 3, and 4 Northern, representing a moisture range of 11 to 17%. The two-stage vacuum oven and Brown–Duvel methods were used as bases of comparison. Regression equations, standard errors of estimate, and data on temperature effects are reported. The standard error of estimate of vacuum oven results was 0.15% for the Brown–Duvel method, 0.23% for the Tag–Heppenstall meter, and 0.28% for the Universal met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1950
1950
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In the majority of studies on dough rheology, linear viscoelastic theory has been assumed (2,4,5,7,8,11,(13)(14)(15)(16)(17). In all cases this assumption is of doubtful validity in view of the magnitude of the strains involved and no attempt has been made to establish the range of deformation over which dough exhibits linear viscoelastic behaviour.…”
Section: A) Egect Of Strain On the Dynamic Modulimentioning
confidence: 99%
“…In the majority of studies on dough rheology, linear viscoelastic theory has been assumed (2,4,5,7,8,11,(13)(14)(15)(16)(17). In all cases this assumption is of doubtful validity in view of the magnitude of the strains involved and no attempt has been made to establish the range of deformation over which dough exhibits linear viscoelastic behaviour.…”
Section: A) Egect Of Strain On the Dynamic Modulimentioning
confidence: 99%
“…Equipment for the measurement and control of humidity [1088,1095,1104,1133,1159,1166] is under development and is particularly important since the effects of moisture on the properties of textile materials are not clearly understood. The evaluation of various electronic meters for determining the moisture content of textiles has been continued [1120,1126,1127,1168] ; and investigations of other instruments and methods for moisture determination in textile materials have also been reported [1092,1130,1160]. The nuclear magnetic resonance absorption technique [1151] ] is reported as a promising method for determining moisture content.…”
Section: Control Instruments Andmentioning
confidence: 99%
“…In a study of the curing of goatskins, Lloyd et al (106) found that rapid drying tended to produce a leather more greasy and susceptible to greater rehydration than slow drying. Cox and Roddy (83) studied paste-drying of leather and found that the tendency of leather to stick during drying was more a function of the condition of the leather grain surface than the type or concentration of the pasting agent. Increased fat in the leather decreased adhesion.…”
Section: Drying Of Specific Materialsmentioning
confidence: 99%